2015
DOI: 10.1016/j.msea.2014.12.090
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and mechanical properties of as-cast quasibinary NiTi–Nb eutectic alloy

Abstract: a b s t r a c tNi 40 Ti 40 Nb 20 is reported in the literature as a eutectic composition in the quasi-binary NiTi-Nb system. Eutectic and near-eutectic alloys find applications in various fields, including hydrogen permeation, energy damping, and liquid phase bonding of NiTi structures. In this study, we examine a cast Ni-Ti-Nb alloy with the above eutectic composition. Prealloyed, near-stoichiometric NiTi powders and pure Nb powders are blended and heated above the eutectic temperature to create a melt with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…Evidently, there are grain‐like colonial regions with an average size of 20–30 μm surrounded by the coarse lamella regions as the colony boundaries. Such a hierarchical structure is the result of a varying cooling rate in metallic melts, which can be controlled by tuning the melt chemistry and cooling rate . Further SEM imaging reveals that each colony consists of the fine lamella structures with the lamella orientation varying from colony to colony, as seen in Figure d.…”
Section: Methodsmentioning
confidence: 97%
“…Evidently, there are grain‐like colonial regions with an average size of 20–30 μm surrounded by the coarse lamella regions as the colony boundaries. Such a hierarchical structure is the result of a varying cooling rate in metallic melts, which can be controlled by tuning the melt chemistry and cooling rate . Further SEM imaging reveals that each colony consists of the fine lamella structures with the lamella orientation varying from colony to colony, as seen in Figure d.…”
Section: Methodsmentioning
confidence: 97%
“…where a 2 is a constant (measure unit K À1 ), A 1 f is temperature of terminating the austenitic phase and M 0 f is temperature of terminating the martensitic phase. Equations (19) and (20) make clear the existence of direct correlation between the temperature and the bending of the plate which describes its thermomechanical behaviour.…”
Section: Figurementioning
confidence: 99%
“…Eqs. (19) and (20) can be used for the calculation of bending in the plate containing SM elements and for the evaluation of minimum force which is necessary aiming to fix a certain shape of the plate. The numerical research has shown that force which is necessary for the counter-bending of plate varies from 370 to 135 N (it is equal to force being triggered by the plate), when temperature varies from 80 to 100°C.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations